PERBEDAAN KADAR GULA DARAH PADA REMAJA SETELAH LARI 12 MENIT DAN 30 MENIT - Febriyanti, Annisa Putri; Huldani, Huldani; Kaidah, Siti; Asnawati, Asnawati; Hendriyono, Hendriyono (Universitas Lambung Mangkurat, 2023)
Blood glucose is the main metabolic fuel in producing energy derived from carbohydrates. Physical activity can bring physiological changes, one of which is to improve overall glucose control. The purpose of this study is to explain why adolescents' blood sugar levels differed after running for 12 and 30 minutes, respectively. Thirty young people were asked to recite using a quasi-experimental model without a control group at the Triwijaya Housing Banjarmasin according to the criteria divided into 15 teenagers running 12 minutes and 15 teenagers running 30 minutes. A purposive sampling strategy is utilized in the sample selection method. Before and after 12 and 30 minutes of running, blood sugar levels were measured. This study obtained an average blood sugar level of 83.8 mg/dL in the group of teenagers after running 12 minutes and 83.4 mg/dL after completing a 30-minute run in the group of teenagers. The results of statistical tests on blood sugar levels performed with the Mann-Whitney alternative test in the adolescent group after running 12 minutes and the adolescent group after running 30 minutes obtained a value of p=0.011. The study's conclusion was that adolescents had different blood sugar levels after running 12 minutes and 30 minutes of moderate intensity.